The mechanisms of reproduction and reduction of inequalities: what do we learn from the research of the Centre for Metropolitan Studies (CEM)? - Gomes, Sandra (2021)
The manuscript discusses the production of the Centre for Metropolitan Studies (CEM) for the last twenty years in the areas of scientific research, transfer of technology and innovation and diffusion of knowledge Throughout its history, the main scientific concern relates to the specification of political, institutional and symbolic mechanisms that explain both the reproduction and the overcoming of poverty and inequalities. The main contributions of CEM, either in the academic field or within the public debate, are presented in this manuscript around three topics. First, the findings on public policy analysis are detailed, including the political and partisan dimensions of governments. In common, all these analysis attempt to specify the effects of policies on social and political inclusion. In the second topic, research results on the studies of spatial distribution of social groups, their living conditions, and the specification of peripheries in urban and metropolitan settings are presented. Third, the manuscript theorises about what could be understood as Brazil’s paradox since the redemocratization in the 1980s: although the social welfare of the population has significantly increased in this period, the inequalities derived from the occupational structure (labour market) remain resilient as markers of income attainment and other forms of inequalities. At the end, some suggestions on further research agenda are made.